SOSIALISASI DAN PELATIHAN PEMBUATAN MAKANAN HERBAL SEBAGAI UPAYA PENGEMBANGAN SUMBER DAYA MANUSIA DESA BRUMBUN - Aziz Rivai; Ajeng Wahyuni (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Brumbun village is a village located in Wungu sub-district, Madiun district, where the village is located at the eastern end near the slopes of the mountains of Madiun City. The place is still beautiful and is flanked by two streams of water originating from the mountains and has a very open, skilled community, accepts input and likes to work together. making this place rich in potential assets. Its abundant and unspoiled natural wealth makes this village dubbed a tourist village that is visited for family vacations and learning facilities. There are many plants that thrive in the village, including those with herbal nuances. Based on the survey, it was found that herbal plants such as moringa leaves and katuk leaves were unfortunately left unattended. Villagers only cultivate plants that are easy to process, such as cassava, tales and rice. Departing from personal assets and the many herbal plants that grow in the village as well as encouragement from the village government. So, the need for training on the manufacture of this herbal food is done. After the training was carried out, the response was positive and the enthusiasm of the PKK women showed that the training was very acceptable, the enthusiasm of the PKK women in the training made the training event run smoothly from start to finish. The evaluation results show that PKK mothers are able to do well. Even so, there is still a need for more assistance related to how to get perfect results and have a selling point.